Non-Hodgkin's lymphoma and occupation in Sweden: a registry based analysis. Issue 1 (January 1993) - Linet, M S; Malker, H S; McLaughlin, J K; Weiner, J A; Blot, W J; Ericsson, J L; Fraumeni, J F
Abstract : Incidence of non-Hodgkin's lymphoma in different employment categories was evaluated from the Swedish Cancer-Environment Registry, which links cancer incidence during 1961 to 1979 with occupational information from the 1960 census. New associations were found for men employed in shoemaking and shoe repair, porcelain and earthenware industries, education, and other white collar occupations. Several findings supported associations found in other countries, including excesses among woodworkers, furniture makers, electric power plant workers, farmers, dairy workers, lorry drivers, and other land transport workers. Risks were not increased among chemists, chemical or rubber manufacturing workers, or petrochemical refinery workers. Caution must be used in drawing causal inferences from these linked registry data because information on exposure and duration of employment is not available. Nevertheless, this study has suggested new clues to possible occupational determinants of non-Hodgkin's lymphoma.